Putting target segmentation theory into practice : an exploratory study on Singapore SMEs. - Lim, Zhixin. (2013)
Over the recent years, increased Singapore governmental efforts and focus in helping the SMEs are evidence of the Small and Medium Enterprises’ (SMEs) importance to the local economy. With over 99% of enterprises in Singapore being SMEs and a contribution of over 50% to 2012’s Gross Domestic Product (GDP), it is imperative to ensure the sustainability of these enterprises. However, despite the abundant policies supporting the SMEs in increasing productivity, the lack of specific industry knowledge and experience are posing challenges to resource-and-knowledge-limited SMEs in continuing or expanding operations and becoming successful. One crucial success factor identified is the target market selection by companies. Hence, this research study aims to provide a guiding descriptive framework with recommendations on industry-specific target market selection patterns which SMEs can utilise when entering into the three sampled industries of Retail Trade, Food & Beverages (F&B) services and Other Service Activities (OSA). The industries selected for this study are in the Business-to-Consumers (B2C) context, with low barriers of entry as well as less resource-intensive. Building on the findings and analyses conducted on the SMEs in the three industries, our group lays out the recommendations to SMEs with reference to dominant industry trends as well as clear exceptions to those trends. We hope that through this research project, SMEs can be better equipped with a guide on how to utilise target market selection patterns in the three industries and be informed of the criteria needed to implement such patterns. Finally, we hope that this research study will inspire more forward research on target market selection in the Singapore SMEs’ context using alternative theories as well as to build upon this research study.